Professores de Street Dance do Estado de São Paulo: formação e saberes - Martins Valderramas, Caroline Guimaraes [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
This research of qualitative nature, aimed to analyze the formation and knowledges of the teachers of Street Dance from the State of São Paulo. Reviewing the literarature it was approached the conceptions of culture, "Hip Hop Culture", and Street Dance. Also, some studies referred to the professional formation in dance and Physical Education; acting in dance by the teacher of Physical Education; and professional academic formation and/or experimental. The approaching method was the story of the time at present. The technique: interview semi-structured. According to the analysis of the statements: a) we noticed that no one of the interviewers show academic formation in dance; a small part is graduated in Physical Education, and the majority act as authorized teachers by the CREF and/ or DRT; b) we verified that the teaching of Street Dance is determined by experimental knowledges. The Street Dance shows itself as a process of constitution, and the formation and the knowledges to its teaching did not show systematization.

A pesquisa de natureza qualitativa objetivou analisar a formação e os saberes dos professores de Street Dance do Estado de São Paulo. Na revisão de literatura abordaram-se temas como: Cultura, “Cultura Hip Hop”, Street Dance, Formação Profissional em Dança e Educação Física; atuação em dança pelo professor de Educação Física e formação profissional acadêmica e/ou experiencial. O método de trabalho foi a história do tempo presente, utilizando como técnica a entrevista semi-estruturada. De acordo com a análise dos depoimentos: a) constatou-se que nenhum dos entrevistados apresenta formação acadêmica em dança; a minoria é formada academicamente em Educação Física e, a maioria, atua como professores autorizados pelo CREF e/ou DRT; b) verificou-se que o ensino de Street Dance é determinado por saberes experienciais. O Street Dance se apresenta em processo de constituição e a formação e os saberes para seu ensino não apresentaram sistematização.
Teachers of Street Dance of the State of São Paulo: formation and knowledge
Keywords: Street Dance; Formation; Knowledges